Adulterated honey consumption can induce obesity, increase blood glucose level and demonstrate toxicity effects - Suhana Samat; Francis Kanyan Enchang; Abdullah Abd Razak; Fuzina Nor Hussein; Wan Iryani Wan Ismail (Penerbit Universiti Kebangsaan Malaysia, 2018)
The effects of adulterated honey consumption towards human health is not widely known; mainly due to lack of systematic and scientific studies and low public awareness. In this study, short-term and long-term effects of consumption on two brands of commercially honey are available in Malaysian market was investigated and compared to normal control (NC) rats and rats fed with natural pineapple honey (PH) using male Sprague dawley rats. Adulteration of honey used in the study was measured using physicochemical and antioxidant analyses and identified as adulterated honey A (FHA) and B (FHB). No toxicity effect was found for short-term consumption (14 days with one honey consumption). However, visible effects were observed after 16 weeks of study. Both FHA and FHB showed a significant increase (p>0.05) in cholesterol (48.6 ± 4.8 mmol/L, 46.5 ± 3.6 mmol/L), triglycerides (26 ± 1.2 mmol/L, 24.4 ± 1.8 mmol/L) and glucose (28.4 ± 2.5 mmol/L, 25 ± 2.6 mmol/L) level respectively. In contrast, rats from NC and PH groups have lower cholesterol (26.5 ± 4.4 mmol/L, 18.94 ± 3.6 mmol/L), triglycerides (17.5 ± 1.2 mmol/L, 13.5 ± 1.5 mmol/L) and glucose (6.4 ± 1.4 mmol/L, 8.0 ± 1.5 mmol/L) level, respectively. The most critical finding was in total five rats from both fake honey groups showed early mortality. This intensive study indicates long-term adulterated honey may harm to human health and required prompt actions from various authorities locally and internationally to avoid other consequences in the future.